Off-label treatment in diabetic retinopathy - de Oliveira Andrade, Luis Jesuino; Santos França, Larissa; Santos França, Luciana; Vinhaes Bittencourt, Alcina Maria; Santos França, Caroline (Revista de Ciências Médicas e Biológicas, 2014)
Introduction: The prescribing a drug without the indications for which the drug was originally approved by regulators is internationally known as prescribing “off-label”. Objective: To describe the off-label therapy in diabetic retinopathy, reported international scientific literature, through an integrative bibliographical review. Method: Integrative review by searching the Medline international database for review of manuscripts. Results: A total 852 scientific productions were identified, and 37 studies were selected by contain information about the off-label therapy in diabetic retinopathy. Conclusion: The practice of off-label prescribing in diabetic retinopathy has benefits, and in some situations is the only treatment available.